2022
DOI: 10.1097/nne.0000000000001342
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Educators' Perceptions and Self-efficacy in Response to COVID-19

Abstract: Background: During the COVID-19 pandemic, nurse educators had to adapt quickly to required changes in nursing education following isolation mandates. Educators worked diligently to provide a quality remote/online educational experience with limited resources. Purpose: The purpose of this review was to explore nurse educators' perceptions and self-efficacy toward the transformation from the traditional face-to-face teaching to remote/online teaching and simulation/laboratory modifications in response to the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Universities need to invest in contemporary technological infrastructure and online learning platforms that are regularly upgraded to grow the opportunities for flexible online learning in the hybrid and blended context and need to employ technical expertise and instructional designers to develop and sustain the digital environment (Riess et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Universities need to invest in contemporary technological infrastructure and online learning platforms that are regularly upgraded to grow the opportunities for flexible online learning in the hybrid and blended context and need to employ technical expertise and instructional designers to develop and sustain the digital environment (Riess et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The nursing faculty perceives nurse educators’ current work environment as undervalued, lacking support, and with limited time to grow and carry the heavy workload ( 25 ). The ideal work environment, as perceived by nurse educators, is one where educators feel valued, can engage in open dialogue, understand situations and share person-centred decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the pandemic, nursing students experienced negative affective learning, mostly in the form of mental health problems and stress, as well as low motivation to learn (Mulyadi et al, 2021;Naciri et al, 2021). These limitations on cognitive, practical, and affective learning may be why meta-analyses and meta-reviews have found moderate to low levels of satisfaction with virtual education during the pandemic (Tabatabaeichehr et al, 2022), which may also explain why nurse educators perceived less effectiveness in nursing education than before the pandemic (Riess et al, 2023).…”
mentioning
confidence: 99%